The Urgency of Building Good Communication in Muslim Families and its Implementation on Children's Mental Health - Suud Sarim Karimullah (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
This study investigates the urgency of building good communication in Muslim families and its implementation for children's mental health. The method used is a literature study by collecting data from articles, books, journals, and other reliable sources. The results showed that building good communication in Muslim families can help improve children's mental health. Less communicative families tend to experience emotional problems such as anxiety, depression, and aggressive behaviour. The role of parents is very important in shaping good communication in the family. Parents must implement effective communication strategies, such as active listening, understanding children's feelings and needs, and providing emotional support. This can help children feel comfortable and open to communicating with parents, thus forming healthy and supportive family relationships. With good communication within the family, children can feel more confident, have a sense of self and security within their family environment, and have better social skills. This can help them cope with the stress and pressure they may experience and ultimately improve their mental health.